Excercise and Gastrointestinal Complaints, an Overview - Sponsiello, Nicola; Salamone, Maurizio; Di Nardo, Veronica; Busa, Francesca; Andreani, Nicolò (Progress in Nutrition, 2021)
Physical activity affects individual’s general health and can influence the gastrointestinal ecosystem. In athletes, various types of gastrointestinal problems can be observed linked to strenuous and continuous physical exercise. Overall, studies suggest that 30-50% of athletes suffer from such ailments. Recent studies have shown that it is possible to intervene through nutrition and food supplements to train the gut and support gastrointestinal health in athletes.